Diseño óptimo de un sistema de transporte de petróleo en Colombia, caso : petróleo producido en la región de la Altillanura con destino a Cartagena (2015)
The thesis project contemplates the analysis and identification of the transportation system or combination of modes of transport that allows minimizing the costs of transporting the oil produced in the Altillanura to the ports of Cartagena, considering the road, rail and river modes The methodology developed is based on a characterization of the demand and supply of transport for the oil produced in the Altillanura, followed by an analysis and description of the main components of intermodal transport with emphasis on road - rail and road - river systems, Subsequently, different corridors that can be used to transport oil from the Altillanura to Cartagena are identified and selected, reaching 35 corridors (15 in unimodal system, 11 in intermodal road-rail system and 9 in intermodal road-river system) estimating for each one of them the respective transportation costs, based on this information, the minimum cost transport model is formulated and worked. The model, in addition to selecting the corridors with lower transport costs in both the nimodal and intermodal systems, allows us to identify the ranges of distance in which the different modes of transport are competitive.